Case reportsPapuloerythroderma of Ofuji in a 41-year-old woman - Terlikowska-Brzósko, Agnieszka; Paluchowska, Elwira; Owczarek, Witold; Majewski, Sebastian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Papuloerythroderma, described by Ofuji in 1984, is characterized by the occurrence of polygonal, erythematous-brown papules, covering the entire skin surface, except skin folds; these changes are accompanied by pruritus and eosinophilia. We report a case of a 41-year-old female patient with melanoerythroderma that has been intensifying since August 2010. The patient’s personal and family history for atopy were negative. No triggering factors were identified in the course of hospitalizations. Preceding infections and neoplasms were excluded. The diagnosis of papuloerythroderma of Ofuji was established on the basis of major and minor criteria proposed by Torchia et al. The patient met all the five major criteria: 1) erythroderma-like eruption formed by coalescence of flat-topped, red-to-brown papules with a cobblestone-like appearance, 2) itch, 3) sparing of skin folds and creases, 4) histopathological exclusion of cutaneous lymphoma and other skin diseases, 5) absence of the causative factors such as tumors, infections, drugs and atopy. Regarding the 5 minor criteria, the patient met the following three: 1) peripheral (33.8%) and tissue eosinophilia, 2) elevated level of the total serum IgE (10935 IU/ml), 3) lymphopenia (6.6%). The patient went into remission after 9-month treatment with cyclosporine at a dose of 3 mg/kg.